Proximate composition and microbial characteristics of processed tiger nut milk (cyperus esculentus) (2020)
This study investigated the proximate and microbial characteristics of processed tiger nut milk. Tiger nut was purchased, processed under standard conditions and subjected to laboratory analysis in triplicates. The result showed that the sample contain 90.7% moisture content. 0.6% crude protein. 2.7% crude fat. 0.1% crude fibre. 0.2% ash and 5.7%> carbohydrate. The microbial toad was found to the higher than the FAO/WHO standard. The pH was found to decrease from 5.5 at preparation to 3.2 after 18 hours. It was concluded that tiger nut milk is a nutritious beverage with high moisture content hut low crude fibre, crude protein, crude fat and ash content. The milk decrease in pH suggested increase in acidity which aids spoilage.